Peer review of the pesticide risk assessment of the active substance trinexapac (variant evaluated trinexapac‐ethyl) - Arena, Maria (EFSA J, 2018)
The conclusions of EFSA following the peer review of the initial risk assessments carried out by the competent authorities of the rapporteur Member State, Lithuania, and co‐rapporteur Member State Latvia for the pesticide active substance trinexapac and the assessment of applications for maximum residue levels (MRLs) are reported. The context of the peer review was that required by Commission Implementing Regulation (EU) No 844/2012. The conclusions were reached on the basis of the evaluation of the representative use of trinexapac as a plant growth regulator on barley (winter and spring) and wheat (winter). MRLs were assessed in rye. The reliable end points, appropriate for use in regulatory risk assessment and the proposed MRLs, are presented. The confirmatory data following the review of existing MRLs according to Article 12 of Regulation (EC) No 396/2005 were also assessed under this conclusion. Missing information identified as being required by the regulatory framework is listed. Concerns are identified.